Scientific Learning Model: Analytical Thinking and Process Skills in Mathematics - kamid, kamid; Kurniawan, Dwi Agus; Nawahdani, Ahmad Mansur (Journal of Education Reseach and Evaluation, 2022)
Education is one of the efforts to improve the intelligence of the next generation of a nation. Education is considered an important and strategic factor in national development, with efforts oriented towards improving the quality of human resources. In dealing with problems in social life, of course, every student needs to develop process skills. The process skills of each student will be honed by itself if students have the will to be better. It relates to physical and mental skills that result in good attitudes and processes. This study aims to determine the relationship between students' analytical thinking and process skills using the problem based learning model and the problem solving model, and to find out the differences between students' analytical thinking and process skills using the  model and the problem solving model. This research uses quantitative research with associative and comparative types of research. For this type of associative research, descriptive statistical tests are used, while for this type of comparative research, assumptions and hypothesis tests are used. The sampling technique used is purvosive sampling with the criteria of students studying mathematics on circle material, the samples taken are 180 students. The results showed that there was a relationship between analytical thinking and student process skills with the problem based learning and problem solving models besides that there was a comparison between analytical thinking and student process skills in both schools. The implication of this research is that the application of the learning model can be used as a means to develop students' analytical thinking skills and process skills in mathematics.